Viability of Escherichia coli Strains After Long Term Storage in Cryoprotective Media - Yagnuk, Yulya; Gurina, Tetiana; Krestetska, Svitlana; Peretyatko, Olena; Sklyar, Nadia; Yagnuk Аndrii; Pakhomov, Oleksandr; Bolshakova, Halyna (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):310